Online personal selling, platform engagement and e-loyalty. (16th July 2021) - Zuo, Na; Khan, Jashim
This research examines the relationship between online shopping mall quality, consumer platform engagement and e-loyalty by examining the mediating role of online personal selling in the above relationship. Non-probability criterion-based purposive sampling resulted in 208 participants participating in this research. Results show a direct relationship between online retail quality and consumer platform engagement, and e-loyalty. Online personal selling plays a mediating role between platform engagement and e-loyalty. Managerially, organisations should enhance shopping platform quality in order to keep customers engaged, embed more online personal selling functions to facilitate e-loyalty.